2010
DOI: 10.1007/s00264-010-1010-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of enzymatic hydrolysed collagen (EHC) vs. glucosamine sulphate (GS) in the treatment of knee osteoarthritis (KOA)

Abstract: This was a 13-week, multicentre, randomised, parallel, double-blind study. One hundred men and women volunteers aged ≥ 40 years with knee osteoarthritis (KOA) were randomised to once daily enzymatic hydrolysed collagen (EHC) 10 g or glucosamine sulphate (GS) 1.5 g for 90 consecutive days. Follow-up took place after two weeks and after one, two and three months. Primary [visual analogue scale (VAS), Western Ontario and McMaster Universities (WOMAC Index)] and secondary outcomes variables, assessed at weeks two,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…There was limited evidence that (1) moxibustion treatment compared with placebo (SMD=0.09, CI −0.24 to 0.43)52; (2) short-term monochromatic infrared energy compared with placebo (SMD=−0.09, CI −0.55 to 0.37)47; (3) methylsulfonylmethane supplementation compared with placebo (SMD=0.42, CI −0.14 to 0.98)44; (4) Tai Chi Qigong compared with no treatment (SMD=0.46, CI −0.17 to 1.09)49; and (5) enzymatic hydrolysed collagen compared with glucosamine sulfate (SMD=0.12, CI −0.28 to 0.53)55 were as effective in improving QoL of individuals with knee OA (figure 6). …”
Section: Resultsmentioning
confidence: 99%
“…There was limited evidence that (1) moxibustion treatment compared with placebo (SMD=0.09, CI −0.24 to 0.43)52; (2) short-term monochromatic infrared energy compared with placebo (SMD=−0.09, CI −0.55 to 0.37)47; (3) methylsulfonylmethane supplementation compared with placebo (SMD=0.42, CI −0.14 to 0.98)44; (4) Tai Chi Qigong compared with no treatment (SMD=0.46, CI −0.17 to 1.09)49; and (5) enzymatic hydrolysed collagen compared with glucosamine sulfate (SMD=0.12, CI −0.28 to 0.53)55 were as effective in improving QoL of individuals with knee OA (figure 6). …”
Section: Resultsmentioning
confidence: 99%
“…These studies were performed according to the Helsinki Declaration under the supervision of medical doctors and were approved by the experimental ethical committees of the Chisso Corporation (Tokyo, Japan). Any negative effects have not been reported by collagen hydrolysate ingestion at 5-10 g/day for 12 weeks in human studies Ohara et al, 2007;Trč & Bohmová, 2011) and the safety of high dose of collagen hydrolysate ingestion (1.66 g/kg body weight) was also confirmed by animal experiments (Wu et al, 2004). The volunteers were informed that the objectives of the present study and the potential risks of ingestion of collagen hydrolysate such as diarrhoea, and abdominal pain.…”
Section: Human Study Designmentioning
confidence: 94%
“…It was found that EHC, versus GS, lowered average pain level significantly at day 90 of testing, and furthermore there was a significant reduction in the WOMAC scores (P<0.05) between the two groups. Once again, EHC was generally well tolerated as well [20].…”
Section: Oral Collagen In Oamentioning
confidence: 99%
“…Nevertheless, it was concluded that PCH was well tolerated and safe to consume by patients [19]. Meanwhile, Kumar et al (2014) reported in their randomised double-blinded clinical trial of 5 g daily twice collagen peptide's effects on patients with knee OA a statistically significant reduction in WOMAC scores when compared to a placebo after 13 weeks [20].…”
Section: Oral Collagen In Oamentioning
confidence: 99%
See 1 more Smart Citation